2001
DOI: 10.1111/j.1349-7006.2001.tb01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Intracellular l‐βD‐Arabinofuranosylcytosine 5′‐Triphosphate in 1‐β‐D‐Arabinofuranosylcytosine Therapy at Low and Conventional Doses

Abstract: 1‐β‐D‐Arabinofuranosylcytosine (ara‐C) is used empirically at a low, conventional, or high dose. Ara‐C therapy may be optimal if it is directed by the clinical pharmacokinetics of the intracellular active metabolite of ara‐C, 1‐β‐D‐arabinofuranosylcytosine 5′‐triphosphate (ara‐CTP). However, ara‐CTP has seldom been monitored during low‐ and conventional‐dose ara‐C therapies because detection methods were insufficiently sensitive. Here, with the use of our newly established method (Cancer Res., 56, 1800‐1804 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
(21 reference statements)
2
13
0
Order By: Relevance
“…2-4). The fact that four of the five cell lines had alterations in ara-CTP-related factors is in agreement with other studies that intracellular activation of ara-C to ara-CTP is the most crucial factor for determination of cellular sensitivity to ara-C (11)(12)(13)(14)18). Our study did not detect an increase in total cellular glutathione, which we previously identified in leukemic cells that were resistant to both ara-C and daunorubicin (36), suggesting that the mechanism of resistance to ara-C of the clones established here might be ara-C-specific.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…2-4). The fact that four of the five cell lines had alterations in ara-CTP-related factors is in agreement with other studies that intracellular activation of ara-C to ara-CTP is the most crucial factor for determination of cellular sensitivity to ara-C (11)(12)(13)(14)18). Our study did not detect an increase in total cellular glutathione, which we previously identified in leukemic cells that were resistant to both ara-C and daunorubicin (36), suggesting that the mechanism of resistance to ara-C of the clones established here might be ara-C-specific.…”
Section: Discussionsupporting
confidence: 77%
“…Since ara-C cytotoxicity depends on ara-CTP incorporation into DNA and therefore depends on ara-CTP concentration, ara-CTP levels thus represent an index of ara-C cytotoxicity. Intracellular ara-CTP levels also have clinical value since a correlation between the intracellular pharmacokinetics of ara-CTP and response to ara-C therapy has been established (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixture was vortexed for 10 s, and allowed to stand for 15 min at 4 • C. The acidic supernatant was isolated by centrifugation of the sample (15,600×g, 20 s, 4 • C), and then mixed with 100 l of 0.5N potassium hydroxide for neutralization. After another centrifugation (15,600 × g, 20 s, 4 • C), the neutralized supernatant was obtained as an acid soluble fraction (ASF), a nucleotide pool [12,15]. The sample loop for the HPLC had a 500-l space, and the dead volume for the aspiration of the sample by the autosampler was 170 l. By adding 500 and 170 l and some room, the volume of each ASF sample was adjusted to 700 l by the addition of water, and the 500-l aliquot was applied to the chromatographic analysis.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…In clinic, no correlation has been found between the therapeutic outcome and F-ara-ATP in treating chronic lymphocytic leukemia [10]. However, as demonstrated in the case of cytarabine, the parameter for predicting the clinical efficacy of a nucleoside analogue is not the plasma drug concentration but its triphosphate form in leukemic cells [11,12]. Therefore, taken together with the understanding of the mechanism of action, the pharmacokinetic evaluation of F-ara-ATP may provide crucial information on scheduling and dosing fludarabine.…”
Section: Introductionmentioning
confidence: 97%